Subjonctif, négation et polyphonie - Donaire, Maria Luisa (HERMES - Journal of Language and Communication in Business, 2017)
This paper will establish (from a semantic perspective, based on the theory of O. Ducrot and J.C. Anscombre) that the subjunctive mode in itself carries instructions for the semantic interpretation of those enunciations in which it takes part. Those instructions conform a dynamics of argumentation based on the specific polyphonic game that makes the subjunctive distinctive from other modes. The negative constitutes a fundamental factor of this polyphonic behaviour insofar as it presupposes the introduction within the enunciation of two opposing viewpoints, one negative, the other positive, and given that the speaker might choose one or the other or maintain the alternative.